CFD-DEM coupling analysis of the negative pressure inlet structural parameters on the performance of integrated positive-negative pressure seed-metering device - Dandan Han; Wei Li; Yunxia Wang; Qing Wang; Zhijun Wu; Yuchao Wang; You Xu; Lijia Xu (Frontiers in Plant Science)
To assess the influence of the structural parameters of the negative pressure inlet pipe on the seeding performance of the integrated positive-negative pressure seed-metering device, angles α and β, along with taper θ, were selected as test variables for conducting coupling simulation tests and physical bench tests. The results indicate that the average differential pressure across the holes in the seed-filling zone (Δpsf), the airflow rate at the interaction interface between the negative pressure inlet pipe and the negative pressure chamber (Q), the average drag force on seeds in the seed-filling zone (FD,sf), and the average drag force on seeds in the seed-cleaning zone (FD,sc) are all significantly affected by the test factors. The structural parameters of the negative pressure inlet pipe can be accurately predicted using the prediction model developed through regression analysis of the central composite test results. The optimal parameters combination is established as 17.1° for angle α, 81.3° for angle β, and 0.52° for taper θ. The maximum error between the predicted evaluation index values and those obtained from the coupling simulation verification test with the optimized negative pressure inlet pipe is less than 6.66%, indicating a strong correlation and reasonable prediction of the structural parameters. The results from the physical bench tests confirm that the optimal operational speed for the seed-metering device with the optimized negative pressure inlet pipe is 4 to 5 km/h, with an optimal working negative pressure of 4 to 6 kPa. Under these conditions, the qualified rate varies from 92.27% to 95.28%, the multiple rate from 2.43% to 5.52%, and the leakage rate from 1.22% to 5.2%.